THE EFFECTIVENESS OF THE TAX REGULATION SOCIALIZATION STRATEGIES ON TAX PAYERS’ COMPREHENSION AND COMPLIANCE IN IMPLEMENTING THEIR TAX OBLIGATIONS - Herawati, Hetti; Tabroni, Roni; Lusiana, Senny (Fakultas Pendidikan Ekonomi dan Bisnis, 2018)
In order to increase state’ earning from tax, government should be active in making society awareness on their obedience to pay tax. This study was based on the importance of tax socialization by the tax office to tax payers through different kinds of media. Socialization has been carried out not only by face to face method, but also by mass media appropriate to the recent situation. The goal of this study was to know the socialization strategies done by the Tax Office for the tax payers both through mass media and directly done by the Representative Accountants. Besides, this study also was to evaluate the effectiveness of these strategies on tax-payers’ comprehension and their obedience. The output of this study was the formalization the appropriate socialization standards for the tax office in order to increase the tax-payers’ awareness and as a result the tax revenue will increase automatically. First stage, this study observed the Tax Office policies especially on the aspect of tax regulation socialization strategies. Further study on the aspect of media itself as the tool for socialization. Finally, this study would have the conclusion about the relationship between socialization methods and the awareness and the obedience of tax payers in tax payment. This study used descriptive associative methods. The first analysis stage was to test the basic assumption i.e. normality test, and then for the hypothesis testing used Path Analysis. This study concluded that there was the positive correlation between socialization strategy on tax regulation and tax payers’ comprehension and the awareness and the obedience of tax payers.